Produção de etanol por sacarificação e fermentação simultâneas a partir do bagaço de caju pré-tratado com Ácido-Álcali - Barros, Emanuel Meneses (2015)
In this work was studied ethanol production from cashew apple bagasse after acid followed by alkali pretreatment (CAB-OH) using theSimultaneous Saccharification and Fermentation (SSF) processes. In SSF process was utilized the yeast Kluyveromycesmarxianus ATCC36907and the enzymatic complex Celluclast1.5L (30 FPU.gcellulose-1). The assays were conducted in 250mL Erlenmeyer flasks with 100mL of culture medium (sodium citrate buffer 50mM pH 4.8, supplemented with yeast extract 1 g/L and ammonium sulfate 1 g/L and the desired bagasse concentration in %w/v), the initial cells concentration was 5 g/L, the temperature was 40°C and 150rpm of rotation. First, a batch process was performed to evaluate the enzymatic supplementation of culture medium with cellobiase (NS50010-Novozymes) with an activity of 60 CBU.gcellulose-1. The supplemented process with cellobiase had the highest ethanol production (30 g/L) and ethanol efficiency (93%) than the non-supplemented and the subsequent studies were performed with supplementation. After, was realized the evaluation of CAB-OH load (7.5, 10, 15 e 20%w/V) in processes with (PSSF) and without pre-saccharification (SSF). The highest ethanol production corresponded to SSF processes with bagasse load of 15%, this being also the highest productivity, and PSSF with bagasse concentration of 20% and these processes were statistic similar within the standard deviation of the samples in relation to ethanol production. However, the SSF and PSSF processes with 10% of dry matter had the highest efficiency (98%) and yield feedstock in ethanol of study (32gEthanol/KgCAB). After, feeding strategies with SSF processes have been made to eliminate inhibitory effects in batch processes with high loadings of solids. There were evaluated feeding strategies: two with initial CAB-OH load of 10% and 20% in the end (a strategy with two feeds and one with four) and another with initial load of 15% and final of 25% (with four feeds). All processes, with the exception of 7.5% load, had %VethanolVsolution-1 above 4% and the fed batch processes reached a similar ethanol production (68 g/L), towering in 17% the ethanol concentration compared to batch process with load of 20%. All processes, with the exception of 7.5 % load, had %Vethanol/Vsolution above 4% and the fed batch processes reached the highest ethanol production of study (68 g/L). The processes with initial load of 10 % and final of 20 % reached a higher efficiency (81 %), but the process that reached the highest productivity was the process with the initial load of 15 % and final of 25 % (2,4 g/L.h), and high ethanol global yield too (32 gEthanol/KgCAB), so this process achieved the best results of present study. Based on the results presented, CAB-OH showed a promising substrate for ethanol production by SSF and PSSF processes, conducted by batch and fed batch method, using high loadings of solids.